2008
DOI: 10.1002/hed.20783
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of osteopontin expression in T1 and T2 tongue cancers

Abstract: Overexpression of OPN in the tumors implicated a more aggressive tumor behavior and was an important factor for survival. In addition, there might be relationship between OPN and CD105 expressions in angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
7
28
1
1
Order By: Relevance
“…[3] However, our findings were similar to many of the previous studies which showed negative OPN expression in oral hyperplasias. [910]…”
Section: Discussionmentioning
confidence: 99%
“…[3] However, our findings were similar to many of the previous studies which showed negative OPN expression in oral hyperplasias. [910]…”
Section: Discussionmentioning
confidence: 99%
“…It can also be induced by VEGF and is involved in vessel angiogenesis and endothelial cell survival [127–129]. Matsuzaki et al [130] failed to demonstrate a correlation between OPN expression and lymphatic metastases and survival in T1-4 tongue cancer, but OPN expression has also been studied in T1-2 tongue cancer using a different means of immunohistochemical evaluation [131]. Thirty out of 94 patients (31.9%) expressed OPN and this significantly correlated with a more advanced T stage (T2 versus T1) ( P = .004), positive lymph nodes ( P < .001), the presence of tumor necrosis ( P = .016), and greater tumour thickness ( P < .001).…”
Section: Osteopontinmentioning
confidence: 99%
“…Petrik et al, suggested plasma OPN is an independent prognostic marker for head & neck cancer [15]. Two studies have been carried so far, to evaluate the expression of OPN in human OSCC [16,17]. To the best of knowledge, this is the first study to analyse the expression of OPN in OSCC and patient matched tumour free surgical margins of OSCC.…”
Section: Methodsmentioning
confidence: 99%